Effectiveness and safety of moderate-intensity aerobic water exercise during pregnancy for reducing use of epidural analgesia during labor: protocol for a randomized clinical trial - Araceli Navas; Catalina Artigues; Alfonso Leiva; Elena Portells; Aina Soler; Antonia Cladera; Silvia Ortas; Margarita Alomar; Marina Gual; Concepción Manzanares; Marina Brunet; Magdalena Julià; et al. (BMC, 2018)
Abstract Background Epidural analgesia during labor can provide effective pain relief, but can also lead to adverse effects. The practice of moderate exercise during pregnancy is associated with an increased level of endorphins in the blood, and this could also provide pain relief during labor. Aerobic water exercises, rather than other forms of exercise, do not negatively impact articulations, reduce edema, blood pressure, and back pain, and increase diuresis. We propose a randomized controlled trial (RCT) to evaluate the effectiveness and safety of a moderate water exercise program during pregnancy on the need for epidural analgesia during labor. Methods A multi-center, parallel, randomized, evaluator blinded, controlled trial in a primary care setting. We will randomised 320 pregnant women (14 to 20 weeks gestation) who have low risk of complications to a moderate water exercise program or usual care. Discussion The findings of this research will contribute toward understanding of the effects of a physical exercise program on pain and the need for analgesia during labor. Trial registration ISRCTN Registry identifier:14097513 register on 04 September 2017. Retrospectively registered.